2013
DOI: 10.1186/1471-2377-13-83
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of sexual dysfunction in women with multiple sclerosis

Abstract: BackgroundThe aim of present study was to determine disease-related and psychological risk factors for sexual dysfunction in women with multiple sclerosis (MS).MethodsThis was a clinical-based study conducted from September 2009 to June 2010 in Tehran, Iran. A consecutive sample of female patients with MS was recruited from an outpatient clinic. The Female Sexual Function Index (FSFI) was used to evaluate sexual function. In addition neurological impairment was measured using the Kurtzke Expanded Disability St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
74
4
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 35 publications
11
74
4
1
Order By: Relevance
“…In the general population, SD and depression are considered to be associated with each other due to a known bidirectional interdependence between depression and SD [12,23]. In female MS patients, previous studies also suggest an interdependence of SD, depression, disease severity, and duration [12,13,24].…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…In the general population, SD and depression are considered to be associated with each other due to a known bidirectional interdependence between depression and SD [12,23]. In female MS patients, previous studies also suggest an interdependence of SD, depression, disease severity, and duration [12,13,24].…”
mentioning
confidence: 93%
“…In female MS patients, previous studies also suggest an interdependence of SD, depression, disease severity, and duration [12,13,24]. However, it is so far unclear whether depression in female MS patients might be secondary to centrally induced SD, or whether SD might result from MS-related depression.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Studying in Turkey, Bektas and Ozkan (36) achieved the results indicating that post-operation body image has been more problematic for women undergoing mastectomy than those having surgery with preserving breast. It seems that the psychological complications have influenced women's sexual function more that the physiological factors because in the majority of the reported studies, the most common sexual problem has been sexuality and arousal .This dimension mainly reflects their psychological status and conditions while the dimensions like sexual stimulation ,vaginal moisture and dyspareunia are caused due to physiological disorders (9). In this research, the most common sexual problem has been found in the sexuality and sexuality arousal dimension.…”
mentioning
confidence: 60%
“…It seems that psychological complications have affected women's sexual function more that the physiologic ones since in the majority of the published studies ,the most common sexual issue has been related to sexuality/sexual arousal dimension . This dimension mainly reflects psychological conditions of patients while areas like sexual arousal, vaginal moisture, and sexual pain stem from physiological conditions causes (9).…”
Section: Introductionmentioning
confidence: 99%